Performance Analysis of LiFePO4 Batteries as a Replacement for Motorcycle Accumulators - nila; Fengky Adie Perdana; Widjanarko Widjanarko; Eva Weddakarti; Chandra Gunawan (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
Conventional motorcycle batteries, including wet and maintenance-free types, suffer from limited lifespan, sulfation issues, and high maintenance requirements. This study proposes a LiFePO4 battery pack as a superior alternative, integrating a real-time monitoring system for enhanced performance tracking. Compared to conventional batteries, the developed system offers longer cycle life, improved thermal stability, and reduced maintenance. The battery pack consists of LiFePO4 cells (3.2V 6Ah) arranged in a 4-series 1-parallel configuration, delivering a 12V 6Ah output while maintaining compatibility with standard motorcycle battery dimensions. Experimental testing validates the system’s ability to monitor current, voltage, and temperature parameters effectively. The integration of a data logging system further ensures long-term reliability and optimization of battery performance. This research contributes to advancing motorcycle battery technology by enhancing durability, safety, and real-time performance monitoring.